Distribution of muscle larvae and antibody dynamics in goats experimentally infected with Trichinella spiralis - Korínková, Karina; Pavlícková, Zdena; Kovarcík, Kamil; Koudela, Bretislav (Parasitology research, 2006)
Herbivorous animals can play a very important role in spreading trichinellosis. In the study presented here, the susceptibility and distribution of Trichinella spiralis infection was examined in 16 goat kids. The goats were inoculated with 10,000 T. spiralis larvae isolated by artificial digestion methods. The animals were necropsied per two animals in weekly intervals, and the larval burdens in different muscle tissue and anti-Trichinella antibodies measured with the indirect enzyme-linked immunosorbent assay (ELISA) serological method using excretory-secretory (E/S) antigen for detecting anti-Trichinella antibodies were assessed during the experiment. T. spiralis larval burden was maximal at 6 weeks postinoculation (480-5,057 larvae/g according to locality), and the larvae were also found in the myocardium (0.77 larvae/g). In this paper, our next step was to compare the specificity and the time of seroconversion by means of ELISA based on E/S antigen prepared from T. spiralis. Antibody response was detected in all 16 goats. The ELISA test carried out showed the first increments in optical density 2 weeks postinfection (p.i.), reached their peak 4 weeks p.i., and remained elevated from that day until the end of the experiment (10 weeks p.i.). These results indicated that specific anti-Trichinella antibodies in goats persist for a relatively long time.
Keywords: Muscles; Antibodies, Helminth; imunoglobulin G; svaly; larva; protilátky helmintové; kozy; nemoci koz; Trichinella spiralis; ELISA; Goat Diseases; zvířata; Enzyme-Linked Immunosorbent Assay; Goats; trichinelóza; Larva; Trichinellosis; Animals; Immunoglobulin G